Reservoir Landslide Physical Modelling under Ice-Snow Melting and Reservoir Water Combined Action - Tongqiang Xiong; Jianlin Li; Lehua Wang; Huafeng Deng; Xiaoliang Xu (Advances in Civil Engineering)
Extreme ice-snow melting in winter affects the infiltration process of snow water on the slope surface significantly and plays an important role in the deformation stability of landslide. Variation in pore water pressure is regarded as an essential factor of landslide instability induced by snow water. In order to figure out the internal relationship between the infiltration process of snow water and the failure mode of deformation and instability of the accumulation landslide, the response law and deformation and failure mode of pore water pressure and soil pressure of landslide accumulation under different ice-snow melting conditions are deeply studied based on the indoor large-scale landslide model test. We have studied the physical model test under the combined action of reservoir water and ice-snow melting. It reveals the seepage erosion deformation and failure mechanism. It undoubtedly provides references of great importance for the geological hazard governance of bank slope in the Three Gorges Reservoir Area.